Hubungan gerakan masyarakat hidup sehat (GERMAS) DENGAN kejadian hipertensi pada usia 20-60 tahun di wilayah kerja Puskesmas Pahandut Palangka Raya - Rahmadita, Annisa; Alexandra, Francisca Diana; Ratnasari, Arini; Widodo, Tri; Arifin, Syamsul (Barigas: Jurnal Riset Mahasiswa, 2023)
Hypertension is a serious problem in Indonesia. The purpose of this study was to determine the relationship between Healthy Living Community Movement (GERMAS) and the occurrence of hypertension at the age of 20-60 years in the Pahandut Public Health Center, Palangka Raya. In this research is an analytic observational study with a cross-sectional study design. The sample in this study was 110 respondents who came from the society in the working area of ​​the Pahandut Health Center. The sampling technique used systematic random sampling. The data obtained came from a questionnaire and was tested for chi square using analysis through the SPSS application.  The results in this study showed that the respondents GERMAS behavior was in the less category (60%) and with a history of hypertension (54.5%). The value means that there is a relationship between GERMAS behavior and the occurrence of hypertension (p = 0.003). There is a relationship between GERMAS behavior and the occurrence of hypertension at the age of 20-60 years in the working area of ​​the Pahandut Public Health Center, Palangka Raya City.